Diagnostic Differences between Obese and Non-Obese Patients Presented with Upper Gastro-Intestinal Symptoms - Saleh, Dr. Mazin; Saleh, Dr. Hamdi; Moin, Dr. Faisal (International Journal of Innovative Research in Medical Science, 2017)
Background: Obesity is associated with various diseases and conditions, particularly cardiovascular diseases, type 2 diabetes mellitus, obstructive sleep apnea, etc. The correlation between upper gastro-intestinal (GI) symptoms and obesity has yet to be completely understood in the presences of many controversial study reports. Aim: To find the impact of obesity on patients with upper GI manifestations through doing Esophagogastroduodenoscopy (EGD). Materials and Methods: A cross sectional study done at Al-Faiha General Hospital, Basra, Iraq; from January 2013 to January 2015; targeting obese patients referred for Esophagogastroduodenoscopy (EGD) clinic complained from upper gastro-intestinal symptoms (heartburn, bloating, epigastric pain, etc.) which were not responded to treatment, had alarming feature(s) or age more than 50 years. EGD was done (by two endoscopist investigators) to the included patients looking for macroscopic abnormalities, in addition to Helicobactor Pylori (H. pylori) testing using urease test (UT). Result: A total of 120 patients with upper GI symptoms were included in this study. Around 51.7% were obese and 48.3% were non-obese. No statistical significances between obesity and ethnicity or gender observed in this study (p-value > 0.05). Thirty percent presented with upper GI symptoms did not have any alarming feature(s); remaining 70% were presented with vomiting, anemia, weight loss, hematemesis and/or melena. Among obese patients, only 6.5% shown normal EGD finding versus 93.5% showed abnormal findings (p < 0.001). Hiatus hernia with esophagitis, gastritis with positive or negative H. pylori and biliary gastropathy showed a statistical difference between obese and non-obese patients with p-values = <0.001, 0.046, 0.021 and 0.002 respectively. Data was analysed using SPSS version 22. Conclusion: Treating physician need to consider EGD more frequently in obese patients who present with upper GI manifestations.